Anulabilidad de las cláusulas abusivas - Correa Valenzuela, Gustavo Andrés (Opera prima (Editorial Universidad del Rosario), 2015)
The thesis analyzes the legal nature of the abusive clauses, particulary in the insurance contract, to proposse the relative nullity as the adequate consequence to the abusive clause.